1.2 Lösning 13
Påstående: Om \( P(x) = x^2 + p\,x + q \) har nollställena \( x_1\, \) och \( x_2\, \) så gäller:
- \[ x^2 + p\,x + q = (x-x_1) \cdot (x-x_2) \]
Bevis:
Nollställena \( x_1\, \) och \( x_2\, \) till \( P(x) \, \) är lösningar till ekvationen \( \; x^2 + p\,x + q = 0 \)
För dem gäller p-q-formeln \( \quad \displaystyle x_{1,2} = -\frac{p}{2}\pm\sqrt{\bigg(\frac{p}{2}\bigg)^2-q} = a_1 \pm a_2 \)
där \( a_1\, \) och \( a_2\, \) är nya beteckningar \( \quad \displaystyle a_1 \, = \, -\frac{p}{2} \quad {\rm och} \quad a_2 \, = \, \sqrt{\bigg(\frac{p}{2}\bigg)^2-q} \)
Vi sätter in \( x_1 = a_1 + a_2\, \) och \( x_2 = a_1 - a_2\, \) i högerledet av påståendet och får vänsterledet:
\[ (x-x_1) \cdot (x-x_2) = (x\,-\,[a_1 + a_2]) \cdot (x\,-\,[a_1 - a_2]) = (x - a_1 - a_2) \cdot (x - a_1 + a_2) = \]
\[ = ([x - a_1] - a_2) \cdot ([x - a_1] + a_2)\,=\,[x - a_1]^2 \, - \, a_2^2\,=\,x^2\,-\,2\,a_1\,x\,+\,a_1\,^2\,-\,a_2\,^2 = \]
\[ =\, x^2\,-\,2 \cdot \left(-\frac{p}{2}\right) \cdot x\,+\,\frac{p^2}{4}\,-\,\left(\frac{p^2}{4} - q\right)\,=\,x^2\,+\,p\,x\,+\,q \]